Pengaruh Pendidikan Kesehatan terhadap Pengetahuan tentang Pemeriksaan Payudara Sendiri (SADARI) pada Remaja - Fitriyah Febriani Ichwanda; Firdawsyi Nuzula; Siswoto Hadi Prayitno (Jurnal Ilmiah Kesehatan Rustida, 2021)
Breast cancer becomes the highest death case in Indonesia for women, which is number 2 after cervical cancer in women. Nowadays, there are still many people who don’t understand the importance of early detection of breast cancer. The purpose of this research was to determine the effect of health education of SADARI through video and voice recordings on adolescent knowledge about SADARI at SMK Al-Azhar Sempu Banyuwangi. The type of research used was Quasi Experimental research with research deign used was Pretest and Posttest with Control Group Design. This research was conducted on July, 2020 with a sample of 32 female student of SMK Al-Azhar Sempu Banyuwangi obtained using total sampling techniques. The population in this research was class XI female student of SMK Al-Azhar Sempu Banyuwangi. The data collection tool used in this research was questionnaire given to research respondents through google form before and after health education was given. The statistical test used was the Kendall-tau test. Research results obtained there is a health education effect through video with the p-value 0,005 and health education through voice recording with the p-value 0,025 as well as from both groups with the p-value 0,000. Statically test shows that health education about SADARI through video is more effective than voice recording. Expected for adolescents to apply SADARI in an early detection of breast cancer.